2022
DOI: 10.3390/chemosensors10020086
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Fast and Red Plastic Scintillators

Matthieu Hamel

Abstract: Radiological detection where Cherenkov residual background can be prominent requires scintillators with increased emission wavelength. Cherenkov residual background precludes the use of UV-emitting sensors such as plastic scintillators. However, the literature is scarce in red-emitting plastic scintillators and only one commercial scintillator is currently available (BC-430, from Saint-Gobain Crystals and Detectors). In addition, X-ray imaging or time-of-flight positron emission tomography (ToF-PET) applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Ref. [40] suggests that a saturation of the scintillator light output at ultra-high dose rate irradiation similar to ionization quenching might happen. According data only exist for electron irradiations and Di Martino et al [ 41 ] have shown for an organic scintillator-based device that saturation sets in above a dose rate of .…”
Section: Discussion Of Dose Rate Effectsmentioning
confidence: 99%
“…Ref. [40] suggests that a saturation of the scintillator light output at ultra-high dose rate irradiation similar to ionization quenching might happen. According data only exist for electron irradiations and Di Martino et al [ 41 ] have shown for an organic scintillator-based device that saturation sets in above a dose rate of .…”
Section: Discussion Of Dose Rate Effectsmentioning
confidence: 99%
“…Unfortunately, there are few scintillators that meet this requirement, as they are usually used in isolation for detection of a specific type of fast neutron or X‐ray. Organic liquid and plastic scintillators with high ET max values are commonly used as effective fast neutron scintillators due to their high hydrogen contents, [ 24,25 ] but the absence of heavy elements makes them several orders of magnitude less effective for detection of high‐energy photons than systems containing high‐Z elements (Figure 1b). ZnS (Ag) and ZnS (Cu) are used in most mainstream scintillators for fast neutron imaging because of their high sensitivities and detection efficiencies for charged particles.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic scintillators are among the most common radiation detection materials used due to their low costs, ease of fabrication, fast response time, and ability to distinguish between neutron and gamma-ray interactions [1]. Plastic scintillators are useful for detector applications relating to national security, radiation therapy, and basic science [2,3].…”
Section: Introductionmentioning
confidence: 99%